PERANAN AUDIT INTERNAL DALAM MENUNJANG EFEKTIVITAS TATA KELOLA KEUANGAN SEKOLAH - Haq, Ahmad Matinul; Imron, Ali (STKIP Pesisir Selatan, 2025)
This study aims to examine the role of internal audit in supporting the effectiveness of school financial governance, particularly in improving institutional performance and establishing transparent and accountable management quality. This research employs a qualitative method with a literature study approach, using the PRISMA model to select, analyze, and synthesize findings from relevant scientific sources. Results the findings indicate that the implementation of internal audit significantly contributes to the effectiveness of school financial governance through several key aspects: (1) auditing compliance with financial governance procedures; (2) assessing and evaluating the implementation of internal control; (3) testing the reliability of accounting data and financial reports for school needs; and (4) evaluating activities to prevent misappropriation and fraud. These efforts enhance the effectiveness of risk management, financial control, and stakeholder trust. The novelty of this study lies in the integration of internal audit with the PRISMA-based literature evaluation model in the context of school financial governance, which has not been extensively discussed in previous studies. Thus, this research provides a new perspective on a more systematic and comprehensive supervisory mechanism to strengthen financial governance in educational institutions.